Observability and observer design for kinetic networks. (3rd August 2009) - Hamraoui, Mohamed; Balde, Moussa; Assala, Noel
In this paper, we deal with the observability and observer design of a certain class of reactors (batch reactors) which are globally asymptotically feedback stabilisable. We show how to design two types of high-gain observers: a Luenberger-like high-gain observer and a high-gain extended Kalman filter. Results of convergence of these estimators follow from our observability analysis. We prove that the non-linear feedback controller using these high-gain observers stabilise such reactors. In fact, we develop an observer-based control structure for a non-linear model of batch reactors. Two examples of such reactors that correspond to strongly connected networks and that have zero deficiency are presented in this paper. Simulations show the good performance of such an observer-based control structure.